Globalisation as a driver of employment precariousness? the labour market status of UK auto workers four years after plant closure. (1st October 2012) - David Bailey; Alex De Ruyter
Abstract : In a context of globalisation and structural change, manufacturing workers in developed countries have been vulnerable to plant closure. This article presents the findings of a longitudinal survey examining the labour market status of ex-auto workers, formerly employed by MG Rover, four years after plant closure. In particular, issues of employment precariousness in terms of employment destinations are considered. The findings suggest that a majority of workers had found employment by April 2008. However, the subsequent experience of economic downturn had left most facing a fragile future on the labour market, suggesting a need for policy measures that go beyond reliance on a flexible labour market to address the inequities faced by workers in such situations.